2011
DOI: 10.3390/ijms12117720
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Compositions, Antioxidant and Antimicrobial Activities of Essential Oils of Piper caninum Blume

Abstract: Chemical composition, antioxidant and antimicrobial activities of the fresh leaves and stems oils of Piper caninum were investigated. A total of forty eight constituents were identified in the leaves (77.9%) and stems (87.0%) oil which were characterized by high proportions of phenylpropanoid, safrole with 17.1% for leaves and 25.5% for stems oil. Antioxidant activities were evaluated by using β-carotene/linoleic acid bleaching, DPPH radical scavenging and total phenolic content. Stems oil showed the highest i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 30 publications
(30 reference statements)
2
26
0
Order By: Relevance
“…The inhibition value (IC 50 ) observed for the oil was significantly higher than that of BHT due to a low amount of phenolic components in the oil (Salleh et al, 2011). Earlier study has shown that kenaf seed oil might actually possess better antiradical activity if compared with some commercial edible oils (canola oil, corn oil and so on) and it can potentially serve as high antioxidative edible oil.…”
Section: Resultsmentioning
confidence: 99%
“…The inhibition value (IC 50 ) observed for the oil was significantly higher than that of BHT due to a low amount of phenolic components in the oil (Salleh et al, 2011). Earlier study has shown that kenaf seed oil might actually possess better antiradical activity if compared with some commercial edible oils (canola oil, corn oil and so on) and it can potentially serve as high antioxidative edible oil.…”
Section: Resultsmentioning
confidence: 99%
“…Mohd Zin et al [10] had carried out antioxidative activity of extracts from Morinda citrifolia L. and had concluded that active compounds in root of the plant might be both polar and nonpolar in nature, whereas compounds that contribute to antioxidative activity of both its leaf and fruit are probably nonpolar in nature. Hakimi Wan Salleh et al [11] studied the chemical compositions and antioxidant and antimicrobial activities of essential oils of Piper caninum Blume. Safrole, β-caryophyllene, β-pinene, and germacrene D were the main components from the leave and stem oil of the plant.…”
Section: Current Approaches Of Research On Medicinal Plants Of Indigementioning
confidence: 99%
“…Antimicrobial tests were determined by the disk diffusion method described by Gulluce et al (2004) with slight modifications as described by Salleh et al (2011). Briefly, 400 mL suspension containing 10 8 CFU/mL bacteria and 10 6 CFU/mL fungal/yeast were spread on NA and SDA mediums, respectively.…”
Section: Disk Diffusionmentioning
confidence: 99%
“…The MIC and MBC were determined by the broth microdilution method using 96-well microplates described by Gulluce et al (2004) with modifications stated by Salleh et al (2011). The inocula of the microbial strains were prepared from 24 h broth cultures and suspensions were adjusted to 0.5 McFarland standard turbidity.…”
Section: Minimum Inhibitory Concentration (Mic) and Minimum Bactericimentioning
confidence: 99%